Tendinose do supra-espinhoso em cães - de Arruda Mistieri, Maria Ligia; Kramer, Martin; Canola, Julio Carlos [UNESP]; Padilha Filho, Joao Guilheme [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
Supraspinatus tendinosis was recently reported in dogs but it is a well-documented disorder in human beings, specie in which is considered the cause of pain and dysfunction in 51% of cases of shoulder problems. It can cause pain and lameness or be asymptomatic in dogs. The clinical relevance in canine specie is unclear and seems to be underestimated. The aim of this paper is to review the possible etiologies involved in this tendinopathy, the main diagnostic methods applied and actual options of therapies in veterinary medicine. Simultaneously, call the clinicians attention to this disorder as differential diagnosis for forelimb pain and lameness diseases.
Supraspinatus tendinosis in dogs
Keywords: Tendinosis; supraspinatus tendon; Dog